Suggestion of an inverse relationship between perception of occupational risks and work-related injuries Sugestão de uma associação inversa entre percepção de riscos ocupacionais e acidentes do trabalho - Ricardo Cordeiro (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2002)
Worker perception of risk influences worker behavior and consequently exposure to risks. However, an inverse relationship between perception of occupational risks and work-related injuries has not yet been clearly established. A matched case-control was performed aiming to investigate possible differences in perception of occupational risks between workers who had suffered occupational injuries and those who had not. Cases were defined as all 93 workers from a large metallurgical factory in southeastern Brazil, who had suffered occupational injuries during the year 1996. Controls were 372 workers who had not suffered occupational injuries, matched on the basis of the factory sector and jobs performed. Assessment of occupational risk perception was performed by asking the workers to fill out a questionnaire consisting of questions on specific risks related to problems in work relations, work per se, and mode of production. The findings suggest that the degree of perception that workers with occupational injuries have of some occupational risks is lower than that of their non-injured coworkers. A percepção que o trabalhador tem dos riscos ocupacionais a que está exposto, influencia seu comportamento e sua própria exposição a riscos. Entretanto, uma relação inversa entre percepção de riscos ocupacionais e acidentes do trabalho, embora especulada, não foi ainda claramente estabelecida. Este é um estudo caso-controle objetivando investigar a existência de diferenças na percepção de riscos ocupacionais entre trabalhadores acidentados e não acidentados. Os casos foram todos os 93 trabalhadores de uma grande metalúrgica de Botucatu, que sofreram acidentes do trabalho no ano de 1996. Para cada caso foram aleatoriamente alocados quatro controles não acidentados, emparelhados segundo a seção de trabalho e a função do trabalhador acidentado na semana do acidente. A mensuração da percepção de riscos ocupacionais de casos e controles se deu analisando-se as respostas dadas pelos trabalhadores estudados a um questionário sobre riscos associados a tarefas específicas, relações no trabalho e organização do trabalho. Os achados sugerem que o grau de percepção que trabalhadores acidentados têm de alguns riscos ocupacionais é menor que o de trabalhadores não acidentados.